Good Governance According To Islamic Perspective - Rusydi, Ibnu (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This paper aims to identify and analyze how governance is thought in Islam perspective. The issue of state leadership in Islam is interesting to study, especially how to find examples of good and clean leadership in Islam. Moreover, one of the global trends of the 21st century is the tendency to implement good governance which is a reference for developing countries in the midst of rampant corrupt government systems. Good governance is a government that guarantees justice, dignity, equality, self-respect and the sharing of development benefits by all. This study concludes that governance in Islam is a state for the benefit, the state is a tool or means to create and maintain benefit. Good and effective governance from an Islamic perspective is based on sharia and siyāsah shar'iyyah. Siyāsah shar'iyyah is Islamic governance and political policy in maintaining the benefit and resisting damage. In essence, the concept of good governance according to the Qur'an is the principle of al-amānah (trusted) and al-'adālah (justice). Honesty and fairness are the basis of a good leader in running his government. In the language of trust means trusted, trusted, honesty, integrity, and responsibility. The state in the view of Islam is a state that prospers and makes its people happy in achieving maqasid al-syariah.